Gel formulation of ethanol extract of mangosteen peel (Garcinia mangostana L.) as a medication for burns in wistar rats - Nining Sugihartini; Rinanda Yeshi Wiradhika (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2017)
Background: Mangosteen peel (Garcinia mangostana L.) has been shown to stimulate the regeneration of damaged body cells and have an antimicrobial activity that can be beneficial in healing burns. Therefore, it is necessary to make it into a gel dosage form that has the advantages of being easily washed with water, high adhesion, cooling of the skin, and good drug release. Objective: To determine the effect of varying concentrations of ethanol extract of mangosteen peel in a gel formulation on wound healing in burns and the physical properties of the gel. Methods: Mangosteen peel extract was obtained by maceration method using ethanol 70%. This extract was formulated in a gel dosage form with variations of extract concentration, namely F I (5%), F II (10%), and F III (15%). The gels were then tested for their physical properties (organoleptic, homogeneity, pH, spreadability, adhesiveness, and physical stability) and their activity against burns experimentally using mice as test animals. Burns were made by using a hot plate with an area of 2 cm x 2 cm. Results: The increase of extract concentration could increase spreadability (p>0.05), adhesiveness (p>0,05), and percentage of healing activity against burns as shown by a significant difference between FI and FIII. On the other hand, the difference in the concentration of the extract did not affect pH (all formulations have pH of 3.5); all formulas also remained homogenous and stable after centrifugation. Conclusion: The best physical properties and wound healing activity for burns was shown by the gel with the ethanol extract of mangosteen peel at a concentration of 15%.